Harmonic Analysis and Mitigation of Electronic Devices Using Passive Filter - Hashim, Hashbullishman (2005)
The objective of this present work is to investigate harmonic profiles of single and three phase non-linear loads and also performance of passive filter that has been designed. The analysis has been carried out using real time harmonic profile measurement equipment. The loads which have been measured are television, video compact disc (VCD) player, sound system, desktop and laptop personal computer (PC) , motor, unintermpted power supply (UPS) and office automation facilities. Passive filter vis-a-vis active filter is used in the experiment because it is maintenance free and of its low cost and trouble free operation. All single phase loads, which were measured, showed that total current harmonic distortions (THDs) are above 100% because they have low fundamental current. Furthermore, most of the harmonic current especially 3rd, 5 th ,7 th , and 9h harmonic order currents were almost 90% of the fundamental current. For three phase system, different types of non-linear loads exhibited different types of profiles. Comparatively, UPS current waveform was more distorted and its THD is higher than motor current waveform. This is because the electronic devices such as UPS, TV, PC etc. are using low current compared to other loads such as central air conditioning system which are not controlled by electronic devices but use chiller for operation. For office load automation facilities at multi storey building, new additional loads can cause the system to become imbalance due to improper wiring connection at DB. Different types of loads and modes of operations can also contribute to cancellation of total harmonic due to phase angle diversity and attenuation of system impedance. In these studies, current harrnonic is more relevant than voltage harmonic because the results show that most of the THDs voltage readings are low compared with THDs current. Results from passive filters showed that the installation of filters can reduce up between 40% - 50% of THD current, output current waveform is improved which is verified by simulations and all currents harrnonic value is increased extensively. This shows that installation of passive filter can resonate the circuit and prevents the harmonic current from flowing.back to the power source which cause only minimum problems to the voltage waveform